"Mixed race" studies : a reader - Ifekwunigwe, Jayne O., 1963- (Routledge, 2004)
Bringing together pioneering and controversial scholarship from both the social and biological sciences as well as the humanities, this book charts the evolution of debates on race and mixed race from the 19th century to the present day.